Classical and neoclassical criminology - Gehring, Krista S. (CrimComics, 2018)
"CrimComics offers a new way to approach criminological theory by engaging students with impactful, highly visual illustrated texts. Each CrimComics Issue traces the development of the theory--placing it in social and political context--and demonstrates its application to the real world. The last page of each Issue features review questions and key terms. Issue 3, Classical and Neoclassical Criminology, begins with introducing students to Cesare Beccaria and Jeremy Bentham, two of the main proponents of the Classical School of criminology. This issue then outlines changes in the United States that led to a resurgence of these ideas in the latter part of the twentieth century, which influenced the development of several neoclassical criminological theories."--